DEVELOPMENT OF WORKSHEET BASED ON SCIENCE, TECHONOLOGY, ENGINEERING AND MATHEMATICS (STEM) TO IMPROVE CREATIVE THINKING ABILITY ON SUBSTANCE PRESSURE MATERIALS - Khadijah Rusdiana Putri Harahap; Ridwan Abdullah Sani; John Adeo Simamora (UNIVERSITAS NEGERI MEDAN, 2022)
Student Activity Sheet (LKPD) is an activity sheet containing tasks carried out by students, containing instructions, steps to complete a task in the form of theory or practice. LKPD can be used to improve students' creative thinking skills because the use of LKPD involves activities such as investigation and thinking activities such as analyzing and solving problems. LKPD development aims to determine the validity of LKPD, student responses and the effectiveness of LKPD in improving creative thinking skills. LKPD development using the ADDIE method, data collection techniques in this study were descriptive analysis and N-gain test. The samples in this study were two design expert lecturers, material experts and learning experts, as well as class VIII and 30 class VIII students of junior high school RK Deli Murni Delitua. Based on the validation of design experts, learning experts and media material experts, students' responses are very good and LKPD can improve students' creative thinking skills, which can be seen from the N-gain calculation, which is 0.71 high category